Synthesis of habitat restoration impacts on young-of-the-year salmonids in boreal rivers - Marttila, Maare; Louhi, Pauliina; Huusko, Ari; Vehanen, Teppo; Mäki-Petäys, Aki; Erkinaro, Jaakko; Syrjänen, Jukka Tapani; Muotka, Timo (Reviews in Fish Biology and Fisheries, 2022)
River restoration offers the potential to enhance biological integrity, often measured as fish population changes. We used a meta-analytical approach to synthesize density responses to in-stream habitat restoration by young-of-the year (YOY) brown trout and Atlantic salmon in 28 rivers (overall 32 restoration projects) in Finland. We also examined which local and watershed-scale factors most influenced restoration success. Finally, we conducted an expert survey to obtain an independent estimate of a sufficient density enhancement for restoration to be considered successful. Despite strong context-dependency, habitat restoration had an overall positive effect on YOY salmonid density. When compared to target levels derived from the expert survey, density responses mainly reached the minimum expected success rate, but remained short of the level considered to reflect distinct success. Variability in restoration responses of trout was linked mainly to river size, predominant geology, water quality and potential interspecific competition (trout vs. European bullhead). Fishing mortality tended to obscure positive effects of restoration and stocking by YOY fish affected negatively trout’s response to restoration, supporting a shift towards self-sustainable schemes in fisheries management. These results imply that habitat restoration is a useful approach for improving the ecological and conservational status of salmonid populations in boreal rivers. To further improve the success rate, and thereby public acceptance, of restorations they need to be complemented by other management measures that enhance the potential for the recovery of threatened salmonid populations.